Circadian clock function does not require the histone methyltransferase MLL3. Issue 7 (15th June 2022) - Baxter, Matthew; Poolman, Toryn; Cunningham, Peter; Hunter, Louise; Voronkov, Maria; Kitchen, Gareth B.; Goosey, Laurence; Begley, Nicola; Kay, Danielle; Hespe, Abby; Maidstone, Robert; Loudon, Andrew S. I.; et al.
Abstract: The circadian clock controls the physiological function of tissues through the regulation of thousands of genes in a cell‐type‐specific manner. The core cellular circadian clock is a transcription–translation negative feedback loop, which can recruit epigenetic regulators to facilitate temporal control of gene expression. Histone methyltransferase, mixed lineage leukemia gene 3 (MLL3) was reported to be required for the maintenance of circadian oscillations in cultured cells. Here, we test the role of MLL3 in circadian organization in whole animals. Using mice expressing catalytically inactive MLL3, we show that MLL3 methyltransferase activity is in fact not required for circadian oscillations in vitro in a range of tissues, nor for the maintenance of circadian behavioral rhythms in vivo. In contrast to a previous report, loss of MLL3‐dependent methylation did not affect the global levels of H3K4 methylation in liver, indicating substantial compensation from other methyltransferases. Furthermore, we found little evidence of genomic repositioning of H3K4me3 marks. We did, however, observe repositioning of H3K4me1 from intronic regions to intergenic regions and gene promoters; however, there were no changes in H3K4me1 mark abundance around core circadian clock genes. Output functions of the circadian clock, such as control of inflammation, were largely intact in MLL3‐methyltransferase‐deficient mice, although some gene‐specific changes were observed, with sexually dimorphic loss of circadian regulation of specific cytokines. Taken together, these observations indicate that MLL3‐directed histone methylation is not essential for core circadian clock function; however, it may influence the inflammatory response.